The Level of Public Trust Analysis in Paying Zakat at BAZNAS Sibolga City - Butar-Butar, Ade Awari; Napitupulu, Rodame Monitorir; Nasution, Hamni Fadlilah (Journal of Islamic Social Finance Management, 2022)
The problem in this study is that the collection of zakat funds at BAZNAS Sibolga City from 2021 has decreased by 16.78%. The decrease in zakat fund collection in BAZNAS Sibolga City occurred due to ineffective management. There are still many people who give their zakat directly to the mustahik and the lack of role of the Sibolga City Government. This study aims to analyze the level of public trust in paying zakat at BAZNAS Sibolga City, North Sumatra. This research is a descriptive quantitative study. The data sources used by researchers are primary and secondary data sources. The data collection techniques used are questionnaire techniques, observations, interviews, documentation, and literature studies. The data analysis used is a descriptive analysis, validity test and reability test using SPSS version 25. The results of this study show that the level of public trust in paying zakat at BAZNAS sibolga city with an interval value of 4.48 which is included in the very high interval category. The trust of the people of Sibolga City is very high in paying zakat at BAZNAS of Sibolga City. Keywords: BAZNAS, Trust, Zakat